The making of religious heritage: Burning churches, fiery emotions, multiple sacralities - Stengs, Irene (Approaching Religion, 2023)
The proliferation of religious heritage seems to flow self-evidently from the processes of de-churching and secularization taking place in many European societies. Although having become redundant or outdated, certain religious buildings, objects or practices may be revalued as religious heritage. This selective setting apart of religious places or practices considered ‘redundant’ as heritage – a value-adding process – involves a form of sacralization. Such processual perspective helps religious heritage to be seen as not just ‘existing’, but, like all heritage, as made. Importantly, the sacredness of religious heritage diverges from the sacredness of religion. With multiple sacralites attributed to it, religious heritage may speak to much larger and diverse audiences as global, national or cultural heritage.